Performance of Broadcast Satellite System Receiver Earth Stations(BSS-ES) Using Ka-band under Effect of Interference from Terrestrial Communication Towers which Operating in the Same Frequency Band in the Syrian Arab Republic - سهاد غانم حلوم (Latakia University Journal -Engineering Sciences Series, 2023)
The research includes a study of the performance of BSS-ES that operate within the ka-band in the Syrian Arab Republic when the satellite downlink is affected by interference from the signals of the terrestrial communications towers and fixed terrestrial stations operating within the same band, The research presents a study of the worst case scenario of the working conditions of the satellite receiving stations by analyzing their performance under the influence of rainy climatic conditions, which greatly affect the quality of the satellite link, especially in the Ka-band BSS, The research includes a study of CNIR, which expresses the carrier To the noise plus interference ratio ,and presented results that help in choosing the height and diameters of the antennas used in the Ka-band BSS receiver stations, according to its geographical location and climatic conditions in order to ensure the quality of the received signal within the required limits.